1982
DOI: 10.1128/aac.22.3.421
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of experimental herpes simplex virus encephalitis with (E)-5-(2-bromovinyl)-2'-deoxyuridine in mice

Abstract: (E)-5-(2-Bromovinyl)-2'-deoxyuridine (BVDU) was examined for its ability to increase the survival rate of mice infected intracerebrally with herpes simplex virus type 1 (strain KOS). BVDU was administered orally (through the drinking water), intraperitoneally, or subcutaneously at doses ranging from 40 to 400 mg/kg per day, starting 0, 2, 4, or 6 days postinfection. Regardless of the route of administration, BVDU effected a significant reduction in the mortality rate of mice infected with herpes simplex virus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
1

Year Published

1983
1983
1990
1990

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…The in vivo effect was almost equivalent to that of E-5-(2-bromovinyl)-2'-deoxyuridine. However, therapeutic efficacies of the antiherpesviral bromovinyl nucleosides we observed were not as marked as those shown by Reefschlager et al (13) for brovavir and by De Clercq et al (2) and Park et al (10) for E-5-(2-bromovinyl)-2'-deoxyuridine. Reefschlager et al (12) also reported a marginal effect of E-5-(2-bromovinyl)-2'-deoxyuridine on intracerebral (i.c.)…”
contrasting
confidence: 39%
See 1 more Smart Citation
“…The in vivo effect was almost equivalent to that of E-5-(2-bromovinyl)-2'-deoxyuridine. However, therapeutic efficacies of the antiherpesviral bromovinyl nucleosides we observed were not as marked as those shown by Reefschlager et al (13) for brovavir and by De Clercq et al (2) and Park et al (10) for E-5-(2-bromovinyl)-2'-deoxyuridine. Reefschlager et al (12) also reported a marginal effect of E-5-(2-bromovinyl)-2'-deoxyuridine on intracerebral (i.c.)…”
contrasting
confidence: 39%
“…However, there have been some discrepancies in the efficacies of antiherpesviral drugs reported by different researchers. For example, treatment with a relatively high dose of either E-5-(2-bromovinyl)-2'-deoxyuridine (400 to 500 mg/kg per day) or brovavir (180 mg/kg per day) caused almost a complete cure rate in mice infected with HSV-1, irrespective of route of virus infection (2,10,12). On the other hand, we had found only a modest effect of brovavir and E-5-(2-bromovinyl)-2'-deoxyuridine in model infections with the VR-3 strain as a challenge virus (6).…”
Section: Discussionmentioning
confidence: 99%
“…The drug has proven beneficial in herpesvirus infections in several animal models (4,6,7,11,16,18). In the only published human trial, oral BVdU limited the severity of herpes zoster in four patients, three of whom had underlying malignancy (3).…”
mentioning
confidence: 99%
“…These concentrations were 10-to 100-fold above usual serum concentrations after oral administration. (E)-5-(2-Bromovinyl)-2'-deoxyuridine compares favorably with currently used antivirals in terms of in vitro myelotoxicity and immunotoxicity.(E) -5 -(2-Bromovinyl)-2' -deoxyuridine (BVdU) is a synthetic pyrimidine deoxynucleoside which has demonstrated significant in vitro activity against herpes simplex virus type 1 and varicella-zoster virus (4,5).The drug has proven beneficial in herpesvirus infections in several animal models (4,6,7,11,16,18). In the only published human trial, oral BVdU limited the severity of herpes zoster in four patients, three of whom had underlying malignancy (3).…”
mentioning
confidence: 99%
“…In studies by De Clercq et al (7,9) with a mouse model of HSV-1 encephalitis, systemic treatment with BVDU was found to be very effective in decreasing the mortality of mice infected by the intraperitoneal or intracerebral route. In the present studies, the efficacy of BVDU in HSV-1-infected Vero cell culture (Fig.…”
Section: Discussionmentioning
confidence: 99%